Protocol for a Qualitative Study: Exploring Loneliness and Social Isolation in Emerging Adulthood (ELSIE). (16th December 2021) - Creaven, Ann-Marie; Kirwan, Emma; Burns, Annette; O'Súilleabháin, Páraic S.
Background: This article describes a protocol for a qualitative study to explore experiences and views and experiences of loneliness and social isolation in young adults, in Ireland. Methods: A youth Research Advisory Group will be consulted on the development of study materials. Our data collection methods will be guided by participant preferences, with potential participants choosing between virtual interviews, focus groups, and an online survey including the open-ended questions contained in the interview/focus group schedule. The data will be analyzed using framework analysis. Discussion: This protocol highlights methodological considerations relevant to a qualitative research study co-designed with young adults. Study findings will be relevant to mental health policy makers and other stakeholders involved in youth mental health.